Governance and Development of Child Friendly Educational Unit (CEA) Models in Indonesia - Vebrianto, Rian; Budiawan, Afiq; Thahir, Musa; Hamzah, Muhammad Luthfi (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
The Child-Friendly Education Unit (Satuan Pendidikan Ramah Anak/CEA) is a significant government program grounded in the Law on Child Protection since 2002 and Presidential Decree No. 36 of 1990, reaffirmed in Article 28C of the Constitution as the state’s commitment to ensuring children’s educational rights. However, various schools still face issues of violence and discrimination. This study aims to explore and analyze the governance and development model of the CEA across different religions and educational levels in Indonesia so that it can serve as a reference and best practice for other institutions. The CEA model is founded on five principles: non-discrimination, the best interests of the child, the right to life and development, respect for children’s views, and good governance. Its implementation involves six components: (1) written policies on CEA, (2) child-friendly learning processes, (3) educators trained in children’s rights, (4) child-friendly infrastructure, (5) child participation, and (6) involvement of parents, communities, the private sector, and alums. This research employs a qualitative approach to in-depth interviews, observations, and document analysis. Respondents were selected purposively from various school levels and religions. At the same time, Meanwhile, qualitative insights were derived from FGDs and interviews. The study identifies empirically tested components and offers strategic recommendations. The research outputs include publications in reputable journals and potential intellectual property rights (IPR). The findings are expected to contribute to national efforts to address root issues in child-friendly education.